Prevalence and Risk Factors of Hypertension Among Male Police Personnel in Urban Puducherry, India - Ganesh, KS; Naresh, AGV; Bammigatti, C (Kathmandu University Medical Journal, 2015)
Background Hypertension is an important health issue among high risk occupation groups like police personnel.Objective To assess the prevalence and risk factors of hypertension among male police personnel.Method This cross sectional study was conducted among male police personnel residing in urban Puducherry, India. Data on blood pressure (BP), anthropometric measurements, demographic factors, smoking, alcohol intake, physical activity, stress level, obesity and dietary factors were collected by interview technique using a standard questionnaire.Result About 296 police personnel were participated. Most of them belonged to the age group of 25-39 years (68%). The prevalence of pre-hypertension and hypertension was 37.8% and 34.5% respectively. Among those with hypertension, 56.86% (58/102) were known hypertensives and 43.13% (44/102) were newly diagnosed. Age group of 50-59 years (AOR=8.472) and 40-49 years (AOR=8.15), currently using alcohol (AOR=1.797), less than 7 servings of fruits in a week (AOR=3.228), moderate stress level (AOR=2.374) and waist circumference more than 90 cm (AOR=4.937) were associated with higher prevalence of hypertension among police personnel.Conclusion Hypertension among Police personnel is comparatively higher than general population in this area. Reduction in alcohol use, increase in fruit servings along with other lifestyle modification measures may help in prevention and control of hypertension.Kathmandu University Medical Journal Vol.12(4) 2014; 242-246